Cup of coffee at the library? Factors influencing consumers’ acceptance of foodservice at the library / Hashim Fadzil Ariffin ... [et al.] - Ariffin, Hashim Fadzil; Mohd Said, Noraslinda; Hamir, Norhamizan; Lahap @ Wahab, Johanudin; Zainol, Noorliza; Ngelambong, Anderson (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Young consumers, especially students, are experiencing the coffeehouse culture or the chill-out factor. Considering these factors as a potential determinant for student to visit a place, library management should take these opportunities to introduce an eatery inside the library. The objective of this study is predominantly to assess the relationship between foodservice acceptance, menu offerings, service quality, environment and price among library users. Questionnaires that consist of foodservice acceptance, menu offerings, service quality, environment and price were distributed to 300 students from 3 public universities in Klang Valley. Findings show that the significant relationships between menu offerings, environment, price and foodservice acceptance are confirmed in Structural Equation Modelling (SEM). On the other hand, service quality indicates the insignificant relationship with foodservice acceptance. The results provide information that can be utilized in understanding, maintaining, and increasing the level of foodservice acceptance that leads to library patronage amongst students. Implications and suggestions for future research are also provided.